A PROPOSAL FOR MODELING AND IMPLEMENTING AN INTEGRATED SYSTEM FOR BRAZILIAN CADASTRES ACCORDING TO ISO 19152:2012 LAND ADMINISTRATION DOMAIN MODEL - Purificação, Nathalia Rose Silva da; Carneiro, Andrea Flávia Tenório; Julião, Rui Pedro (Boletim de Ciências Geodésicas, 2019)
This article proposes the modelling and implementation of an integrated system for Brazilian cadastres, based on the standardized model of land administration described in the ISO 19152:2012 LADM. The model was developed from the identification of the essential elements of the urban, the National Rural Cadastre System and the cadastres of public assets of the Secretariat of the Patrimony of the Union. At all stages of this work, free and/or open source software was used to validate this proposal. The results confirm the viability of the application of the concepts proposed by LADM to the Brazilian system of cadastres, allowing the integration between the systems of different institutions. The model is flexible and allows for the inclusion of additional classes according to changing needs of land administration data users. The current form of the model can be regarded as the basic module to be used as a starting point in the structuring of the National System of Management of Territorial Information, which is aimed at the integration of all existing cadastres and land registries in Brazil.